2020
DOI: 10.1016/j.neubiorev.2020.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Multiple large-scale neural networks underlying emotion regulation

Abstract: Recent models suggest emotion generation, perception, and regulation rely on multiple, interacting large-scale brain networks. Despite the wealth of research in this field, the exact functional nature and different topological features of these neural networks remain elusive. Here, we addressed both using a well-established data-driven meta-analytic grouping approach. We applied k-means clustering to a large set of previously published experiments investigating emotion regulation (independent of strategy, goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
140
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(152 citation statements)
references
References 96 publications
10
140
0
2
Order By: Relevance
“…Macaques exposed to an ‘obesiogenic’ diet, which offered calorically dense food in addition to chow versus those offered chow only (healthy diet) in a randomized controlled trial, gained significantly more weight over a year and exhibited decreased orbitofrontal cortex (BA 11 and 13) to nucleus accumbens functional connectivity as well as greater peripheral inflammation (C-reactive protein), ( Godfrey et al, 2018 0; Godfrey et al, 2020 ). In this trial, stress appeared to have an interactive effect with the obesiogenic diet unlike the chow-only diet by not resulting in Dopamine 2 receptor binding in this orbitofrontal cortex (BA 11 and 13) region, suggesting that stress and regulation of stress ( Morawetz et al, 2020 , Chase et al, 2020 ) may further disrupt orbitofrontal cortex functioning. Human controlled trials of diet interventions examining neural response to palatable food pictures or high-fat high-sweet food have also shown that weight loss is associated with change in orbitofrontal cortex activity ( Murdaugh et al, 2012 , Chen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Macaques exposed to an ‘obesiogenic’ diet, which offered calorically dense food in addition to chow versus those offered chow only (healthy diet) in a randomized controlled trial, gained significantly more weight over a year and exhibited decreased orbitofrontal cortex (BA 11 and 13) to nucleus accumbens functional connectivity as well as greater peripheral inflammation (C-reactive protein), ( Godfrey et al, 2018 0; Godfrey et al, 2020 ). In this trial, stress appeared to have an interactive effect with the obesiogenic diet unlike the chow-only diet by not resulting in Dopamine 2 receptor binding in this orbitofrontal cortex (BA 11 and 13) region, suggesting that stress and regulation of stress ( Morawetz et al, 2020 , Chase et al, 2020 ) may further disrupt orbitofrontal cortex functioning. Human controlled trials of diet interventions examining neural response to palatable food pictures or high-fat high-sweet food have also shown that weight loss is associated with change in orbitofrontal cortex activity ( Murdaugh et al, 2012 , Chen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 69%
“…Whole-brain voxel-based morphometry studies were included in the primary analysis to confirm differences between individuals in the overweight and obese body mass index range relative to those in the healthy body mass index range ( Centers of Disease Control, 2020 ). Large-scale connectivity meta -analyses have shown that brain regions do not typically act in isolation but rather in a network with other regions ( Alves et al, 2019 , Riedel et al, 2018 , de la Vega et al, 2016 , van den Heuvel and Sporns, 2013 , Morawetz et al, 2020 , Chase et al, 2020 ). Given this, we next explored the brain regions that are typically coactive with the areas associated with body mass index that were identified in our primary meta -analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging studies use a similar paradigm to investigate the neural substrates of reappraisal processes in healthy (see e.g., Mulej Bratec, et al, 2015;Mulej Bratec, et al, 2017;Xie, et al, 2016) and clinical populations (see e.g., Larabi, et al, 2018;Heller, et al, 2009). Successful reappraisal in healthy individuals has been shown to depend on the proper interactions between limbic regions, responsible for 'bottom-up' emotional responses and frontoparietal regions, responsible for 'top-down' cognitive control of emotions (Buhle, et al, 2014;Kohn, et al, 2014;Langner, et al, 2018;Morawetz, et al, 2020). However, findings from clinical studies have yielded heterogeneous and often conflicting results (Hofmann, et al, 2012;Zilverstand, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, each ER‐related seed consisted of several concatenated regions: (a) evaluation (VLPFC as the functional surrogate of left and right inferior frontal gyrus [IFG]), (b) initiation (DLPFC as the functional surrogate of pre‐central gyrus and right MFG) and (c) execution (angular gyrus, pre‐supplementary motor area [pre‐SMA] and SMA). Our large‐scale seeds were not compartmentalized to provide a more complete and coherent appreciation of the affective substrates (see [Lindquist, Wager, Kober, Bliss‐Moreau, & Barrett, 2012; Morawetz et al, 2020] for existing debate regarding the locationist vs. constructionist perspectives, where the former assumes affective processes as independent neurobiological foundations, and the latter assumes affective processes as consequences of network interactions). Therefore, the ALFF and FC values were averaged across the regions associated with each large‐scale seed.…”
Section: Methodsmentioning
confidence: 99%